Echocardiography training for cardiac surgery residents: results of a Canadian needs assessment. Issue 1 (December 2016) - Fatani, Mazin; Lachapelle, Kevin; Bhanji, Farhan; McLeod, Peter
Abstract Background In assessing an unstable patient post cardiac surgery, echocardiography can be an essential tool as part of this assessment. However, it may be under-utilized for several reasons. We conducted this study to determine the perceived needs and training objectives for echocardiography training for cardiac surgery residents. Methods This study was a cross-sectional, stratified national survey of cardiac surgery residents, cardiac surgeons, cardiac surgery program directors and cardiologists, designed to acquire opinions on what type and level of objective-based training in echocardiography is required for cardiac surgery residents. Recruitment of survey subjects was through Fluid Surveys email invitations to 201 physicians. Participants were asked to rate the importance of focused echocardiography training for cardiac surgery residents and also give a grade of importance for 18 training objectives. Results We received 89 completed surveys. More than 80 % of responders feel that echocardiography training should be required for cardiac surgery residents. Forty seven percent of all responders felt that residents should take an echocardiography course with or without a rotation to train in echocardiography. Thirty five percent felt that current training in most programs, which entails a single rotation in echocardiography, is sufficient. Seven training objectives were identified as important by more than 80 % of participants. Conclusion Study participants believe that cardiac surgery residents require echocardiography training. The majority agree that echocardiography training should be informed by the identified 7 training objectives.